Sineb El Masrar, Muslim Men. Wer sie sind, was sie wollen, Herder, Freiburg – Basel – Wien 2018, s. 255 - Romejko, Adam (Studia Gdańskie, 2019)
Sineb El Masrar, Muslim Men. Wer sie sind, was sie wollen, Herder, Freiburg – Basel – Wien 2018, s. 255